Leitura mítico-simbólica do romance O Ladrão de Raios - Santos, José Victor Soares Rocha dos (2024)
Myths, present in the most different fields of scientific knowledge, constitute a fundamental bridge between the conscious and unconscious of humanity, making possible to elucidate certain historical facts and human behaviors through them. In this sense, Campbell (2004) proposed the existence of a basic myth to all others, characterized by a heroic journey and transformation, strongly related to the process of identity search proposed by Jung. Thus, as the general objective, this research proposes to investigate how the protagonist of the corpus experiences the heroic trajectory proposed by Joseph Campbell. Regarding the problematic, it also sought to elucidate questions such as definitions of myth and its psychological and literary importance for humanity; the functions of the myth; what kind of hero does Percy represent; whether Riordan merely repeats Campbell or whether he also alters it; what types of monsters are featured in the narrative; among other questions. As the justification for the research, it was brought the defense of myth, a theme often seen as inferior as it does not necessarily portray reality in a literal way, but which greatly contributes to different fields of knowledge, such as literature, psychology, anthropology, between others. For the methodology, qualitative research of an exploratory nature was carried out, using bibliographic and documentary sources. The research was divided into two chapters, the first one being theoretical, using mainly studies by Mielietinski, Patai, Eliade, Durand, Jung and Campbell to outline the history and relevance of the myth to literature, and the second one analytical, dealing with of symbols and stages present in Percy Jackson's journey, exploring the corresponding individuation process. At the end of the analysis, it was found that the structure of Percy's journey is almost completely followed along the lines proposed by Campbell.